Estimation of Runoff Volume for a Watershed in Upper Damodar Valley - Bhattacharya, A.K.; Gopinath, G; Mukherjee, R.K. (Journal of Soil and Water Conservation, 2022)
Hydrological data from a selected watershed in Upper Damodar Valley were used to develop graphical multivariable coaxial relation for predict-ing runoff volume from rainfall volume. This paper outlines the techniques employed and presents the results obtained.